Military Regimes and Nigeria’s Economic Development, 1966-1999 - OYEWALE, Peter Oluwaseun; OSADOLA, Oluwaseun Samuel (Journal of Social Economics Research, 2018)
This paper examines the military regimes and their various efforts at developing the economy of Nigeria. Economic development and growth have little or nothing to do with military duty or responsibility in any sovereign state. They are supposed to be specialists in ammunitions and war-related strategies. The various military take-overs in Africa during the 1950s and 1960s changed the political and economic administration of the countries involved. Aside from the civil wars that affected most of these countries, economic recessions also nearly brought them to their knees. Nigeria as a major factor in Africa and West Africa politics as at this period also had her fair share of military dictatorial regimes that gave room for a complete change of administration control and nation-building. The paper which derives its data from majorly secondary source employs descriptive and analytic methods in analyzing the data of the study.